2020
DOI: 10.1177/0300060520964349
|View full text |Cite
|
Sign up to set email alerts
|

A rare case of short-lasting unilateral neuralgiform headache with conjunctival injection and tearing with progression to neuromyelitis optica spectrum disorder

Abstract: Short-lasting unilateral neuralgiform headache with conjunctival injection and tearing (SUNCT) is a rare primary headache syndrome. However, some cases of secondary SUNCT are attributed to underlying diseases such as demyelination. We herein report a case of SUNCT with progression to neuromyelitis optica spectrum disorder (NMOSD). A 43-year-old woman developed headaches; 6 weeks later, she developed bilateral visual loss and numbness on the left side of her body. She was ultimately diagnosed with NMOSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It has recently been reported that several clinical cases in A-GFAP-A [16,18], MOGAD [15,24,25], and AQP4-IgG+NMOSD [17,26] presented with initial symptoms including headache, fever, meningeal irritation and prominent leukocytosis in CSF are easily misdiagnosed as intracranial infection especially tubercular meningitis, which frequently lead to delayed autoantibody detection and initiation of immunotherapy. Because the neural autoantibody testing is not widely applied in the clinic practice and the available microbiological tests for the diagnosis of tubercular meningitis continue to be a clinical challenge, clinicians meet several challenges in the diagnosis and treatment before the autoantibodies con rmation.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that several clinical cases in A-GFAP-A [16,18], MOGAD [15,24,25], and AQP4-IgG+NMOSD [17,26] presented with initial symptoms including headache, fever, meningeal irritation and prominent leukocytosis in CSF are easily misdiagnosed as intracranial infection especially tubercular meningitis, which frequently lead to delayed autoantibody detection and initiation of immunotherapy. Because the neural autoantibody testing is not widely applied in the clinic practice and the available microbiological tests for the diagnosis of tubercular meningitis continue to be a clinical challenge, clinicians meet several challenges in the diagnosis and treatment before the autoantibodies con rmation.…”
Section: Discussionmentioning
confidence: 99%